Research Development in Informal Inferential Reasoning: Desarrollo de la Investigación en Razonamiento Inferencial Informal - A., Jesús G Lugo (2019)
This paper reports on a Systematic Literature Review (SLR) based on the automated search in WoS, Scopus, MathEduc and, additionally, manually in SERJ. The aim is to provide an overview of the development of research in Informal Inferential Reasoning (IIR) for researchers in Statistical Education. From the search results, 57 primary studies were selected, identifying the emphasis, context and methodology; as well as the most cited authors and articles. It was found that in recent years, the development of research in the IIR has focused on the modeling and use of dynamic software; the results are aimed at researchers and professors. It should be noted that the articles with the greatest impact, in terms of the number of citations or average citations per year, are those previous studies that are considered essential within Statistical Education, since they propose a framework focused on integration of concepts or statistical ideas as a system for the development of the RII.